Pelatihan Perangkat Pembelajaran Berorientasi Higher Order Thinking Skilss (HOTS) Bagi Guru Sekolah Dasar - Rahmawati Patta; Patta Bunda (STKIP Andi Matappa, 2021)
Problems in the field are still many teachers who have not been able to compile Higher Order Thinking Skills (HOTS) oriented assessments, and have not been able to understand the meaning of HOTS. Generally, they immediately want to compile HOTS questions without being based on HOTS-oriented learning tools themselves. In this activity the participants will participate in practicing preparing learning tools, starting competency analysis, developing lesson plans and student activity sheets, as well as reading materials which all lead to the HOTS assessment. The expected output target is that the participants have an example of a HOTS nuanced learning tool that can be applied in the daily learning process. The activity plan is divided into two stages: First Stage: Providing material from resource persons in the form of: (a) development of learning tools in accordance with curriculum demands, (b) understanding of Higher Order Thinking Skills (HOTS), and steps for preparing tools (RPP, LKPD, Teaching Materials, and Assessment). The second stage, the workshop directly practiced developing HOTS-oriented learning tools. Thus, each participant will have a set of HOTS-nuanced learning tools that can be applied to other themes in the curriculum. The participants were able to arrange the assessment instrument grid and arrange HOTS question cards on the theme they chose. There are several supporting factors in this activity because the participants have already attended training for the preparation of learning tools so that they do not have too much trouble modifying the equipment with HOTS content. The obstacle that needs to be overcome is how to familiarize the teachers so that evaluation is not just a rote memory but at a higher level.